Feasibility of Digital-based Flipbook Teaching Materials to Improve Learning Outcomes of Grade V Elementary School Students - Tri Wulandari; Atip Nurharini (Jurnal Pendidikan dan Pengajaran, 2023)
Teaching materials are one of the important components in learning. The use of printed teaching materials does not contain complete material so that it makes the low learning outcomes of students. This study aims to analyze the feasibility of digital-based flipbook teaching materials for plate dance floor patterns as a solution to improve student learning outcomes. This research method is Research and Development (RnD) developed with the ADDIE model. The subjects of this study were material experts, digital teaching material experts, teachers and fifth grade students. The method used to collect research data through observation, interviews, and questionnaires were used to obtain assessment data from material experts, digital teaching material experts, students, and teacher responses. The data analysis techniques used are qualitative and quantitative data. The result showed thar the feasibility of digital-based flipbook teaching materials from material experts was 91,5% with a very feasibility category, while the result of the validation of digital teaching material experts were 95% with a very feasibility category. The results of this study indicate that digital-based flipbook teaching materials for plate dance floor patterns are suitable for use in learning dance in elementary schools.